(untitled) (Research, Society and Development, 2022)
Although implant rehabilitations are successful, a small portion of patients may present peri-implant mucositis and peri-implantitis due to the bacteria biofilm formation. The purpose of the present study was to evaluate the presence of Porphyromonas gingivalis (Pg), Prevotella intermedia (Pi), Fusobacterium nucleatum (Fn) and Scardovia wiggsiae (Sw) in Peri-implant gingival Fluid (PGF) of patients who received implants 12 months ago and associated with periodontitis (PD) history and clinical data. Samples were collected from 44 volunteers and analyzed by PCR with specific primers. The results showed that Pg were detected in 34%, Fn and Pi, 81.8%, and Sw 75% of the volunteers. Pg was frequently detected in patients who had a history of PD (p<0.05, q=8.19), but no statistically significant differences for Fn, Pi, and Sw (p>0.05, q<0.61). Pg was detected in 58.3% of the volunteers who had teeth prior to implants and their presence was associated with periodontitis (p<0.05, q=5.31) and gingivitis (p<0.05, q=4.31). All the patients whose probing depths were greater than 3 mm had Fn in detectable levels (p<0.05, q=4.56). In conclusion, the involvement of Sw in peri-implant alterations was not evident in this work. The presence of Pi and Fn were not related to history of PD and mucositis. Fn was present in periodontal pockets above 3 mm, suggesting its involvement in peri-implant alterations. Pg was detected in patients with a history of PD, gingivitis, and periodontitis and in those who had teeth before the implant installation.